Pengembangan FS-CPSM (Feedback System-Based Creative Problem Solving Metaverse) Menggunakan Game Edukasi Mitigasi Banjir Berbasis Roblox Studio - Mochammad Afdal Susilo Aji; Achmad Junaidi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Flooding in Indonesia is becoming increasingly frequent. Data from the National Agency for Disaster Countermeasure (BNPB) records an average of over 3,000 flood events annually over the past decade (BNPB, 2023). Meanwhile, classroom instruction on flood mitigation often relies on lectures and lacks direct student engagement. This study developed FS-CPSM (Feedback System-Based Creative Problem Solving Metaverse), an educational game created in Roblox Studio that integrates the six-stage Creative Problem Solving (CPS) framework into a fictional post-flood village environment. Players are guided through an interactive interface spanning stages from "Mess Finding" to "Acceptance Finding" supported by an automated feedback system that provides validation and hints when answers are incomplete. The study employed a Research and Development (R&D) methodology with functional testing. Results showed that all 12 key features ranging from the CPS interface and the Sumatra flood story panel to the feedback system operated without errors, achieving a 100% system success rate. This research demonstrates that Roblox Studio is a viable platform for educational games based on structured problem-solving.